Development of Golf World Game Using Roblox Platform - MAT YUNUS, MUHAMMAD IZZAT; Ismail, Azizan (Applied Information Technology And Computer Science, 2026)
The Golf World Game is a unique educational game created using Roblox platform. The purpose of this game is to combine and aim to blend entertainment with learning in one game. However, most golf games nowadays are lack of educational content. These games does not teach players the fundamental ideas and skills related to the game of golf. Instead, they focus mostly on entertaining and interactive gameplay. To tackle this issue, Multimedia Mobile Content Development (MMCD) is used to develop the project. MMCD is a structured methodology used to create games that combine multiple types of multimedia elements, including text, photos, audio, video, and animations. This Golf World Game was developed in the Roblox Studio platform, and this project is designed for UTHM students, especially those interested in learning about golf. The expected result for this game is an enjoyable and informative golf game that will improve players' knowledge while delivering an interesting gaming experience.